Alignment of a 1.2-Mb chromosomal region from three strains of Rhodobacter capsulatus reveals a significantly mosaic structure. - Nikolskaya, T (1995)
High-resolution physical maps of the genomes of three Rhodobacter capsulatus strains, derived from ordered cosmid libraries, were aligned. The 1.2-Mb segment of the SB1003 genome studied here is adjacent to a 1-Mb region analyzed previously [Fonstein, M., Nikolskaya, T. & Haselkorn, H. (1995) J. Bacteriol. 177, 2368-2372]. Probes derived from the ordered cosmid set of R. capsulatus SB1003 were used to link cosmids from the St. Louis and 2.3.1 strain libraries. Cosmids selected this way did not merge into a single contig but formed several unlinked groups. EcoRV restriction maps of the ordered cosmids were then constructed using lambda terminase and fused to derive fragments of the chromosomal map. In order to link these fragments, their ends were transcribed to produce secondary probes for hybridization to gridded cosmid libraries of the same strains. This linking reduced the number of subcontigs to three for the St. Louis strain and one for the 2.3.1 strain. Hybridization of the same probes back to the ordered cosmid set of SB1003 positioned the subcontigs on the high-resolution physical map of SB1003. The final alignment of the restriction maps shows numerous large and small translocations in this 1.2-Mb chromosomal region of the three Rhodobacter strains. In addition, the chromosomes of the three strains, whose fine-structure maps can now be compared over 2.2 Mb, are seen to contain regions of 15-80 kb in which restriction sites are highly polymorphic, interspersed among regions in which the positions of restriction sites are highly conserved.